E-Word of Mouth Brand Bittersweet by Najla via TikTok - Christine Angela Chandra; Teguh Dwi Putranto; Beatrice Angellie; Tesa Marisa (Jurnal Komunikasi Global, 2023)
E-word of mouth is a new marketing communication strategy that has emerged with the rapid development of social media. The rapid growth of TikTok the implementation of this marketing communication strategy. This study aims to analyze the use of TikTok as a platform for Bittersweet by Najla to promote and create e-word of mouth. This research also seeks to analyze the cognitive process of Bittersweet by Najla consumers before making a purchase decision by employing the Elaboration Likelihood Model. The research methodology utilized a case study method by Robert K. Yin, offering a detailed overview of the e-word of mouth communication strategy used by Bittersweet by Najla. The chosen data analysis technique is pattern matching. The findings reveal that a consumer claimed to purchase Bittersweet by Najla products due to the influence of TikTok content and video reviews uploaded on TikTok. Consequently, it can be concluded that the e-word of mouth marketing communication strategy remains effective in this era, and TikTok can be considered a complementary application that supports the success of e-word of mouth marketing communication due to its high user base.E-word of mouth merupakan strategi komunikasi pemasaran baru yang muncul bersamaan dengan perkembangan media sosial yang semakin pesat. Penggunaan TikTok yang semakin pesat menyebabkan strategi komunikasi pemasaran ini menjadi semakin mudah untuk dilakukan. Penelitian ini bertujuan untuk menganalisis penggunaan TikTok sebagai platform bagi Bittersweet by Najla dalam melakukan promosi dan sarana menciptakan e- word of mouth. Penelitian ini juga bertujuan untuk menganalisis proses kognitif konsumen Bittersweet by Najla sebelum melakukan pembelian terhadap produk dengan menggunakan Elaboration Likelihood Model. Metode penelitian yang dipakai dalam penelitian ini adalah metode studi kasus dari Robert K. Yin guna untuk memberikan gambaran detail terkait strategi komunikasi e-word of mouth yang digunakan oleh Bittersweet by Najla. Analisis data dalam penelitian ini adalah teknik pencocokan pola. Hasilnya adalah konsumen mengaku melakukan pembelian produk Bittersweet by Najla karena pengaruh konten TikTok Bittersweet by Najla dan reviu video yang diunggah di TikTok. Hal ini menunjukkan bahwa strategi komunikasi pemasaran e-word of mouth masih efektif di era ini, dan TikTok dapat menjadi salah satu aplikasi pendamping yang dapat menunjang keberhasilan komunikasi pemasaran e-word of mouth karena tingginya pengguna TikTok saat ini.